Synthesis and Kinetic Characterisation of Water‐Soluble Fluorogenic Acyl Donors for Transglutaminase 2. (30th May 2016) - Wodtke, Robert; Schramm, Georg; Pietzsch, Jens; Pietsch, Markus; Löser, Reik
Abstract: Small glutamate‐containing peptides bearing coumarin derivatives as fluorescent leaving groups attached to the γ‐carboxylic acid group of the Glu residue were synthesised and investigated with regard to their potential to act as substrates for transglutaminase 2 (TGase 2). Their synthesis was accomplished by an efficient solid‐phase approach. The excellent water solubility of the compounds enabled their extensive kinetic characterisation in the context of TGase 2‐catalysed hydrolysis and aminolysis. The influence of the coumarin skeleton's substitution pattern on the kinetic properties was studied. Derivatives containing 7‐hydroxy‐4‐methylcoumarin (HMC) revealed properties superior to those of their 7‐hydroxycoumarin counterparts; analogous amides are not accepted as substrates. Z‐Glu(HMC)‐Gly‐OH, which exhibited the best substrate properties out of the investigated derivatives, was selected for representative kinetic characterisation of acyl acceptor substrates and irreversible inhibitors. Abstract : Fluorimetric assay for Transglutaminase 2 : A set of fluorogenic acyl donor substrates for transglutaminase 2 was synthesised by a modular solid‐phase strategy. Their good aqueous solubility allowed for a detailed kinetic characterisation with regard to their TGase 2‐catalysed hydrolysis and aminolysis. Their applicability to characterising amine substrates and inhibitors of TGase 2 was also demonstrated.